Ashabiyah Polarization of the Religious Diversity of Tanon Community Kediri - Hanik, Umi (Tribakti: Jurnal Pemikiran Keislaman, 2023)
Ashabiyah is the most crucial thing in building integrity in the community's social life, especially in religious life. In Indonesia, various kinds of religions have developed, and differences in ethnicity, race, and language are unique features and challenges for the people of Indonesia. What's more, when talking about religion which is very risky in the history of the world and even in Indonesia, discrimination, violence, intolerance, and violence in the name of religion often become prolonged conflicts. Therefore, this research is presented as a sample form of the polarization of ashabiah from the Tanon community, which has differences in one social unit, even at a more micro level, that's the family. This research is qualitative research with a phenomenological approach as the chosen approach. The design strategy that the researcher uses is to identify the nature of a community phenomenon based on the experiences of individuals who are members of the Tanon Village community, Papar District, Kediri Regency. The theory used is Talcott parson's theory of structural functionalism. The results of this study indicate that the function of the religious elite, abangan, and the Tanon community in the salvation system is one of the forums for building religious harmonization. In addition, the religious elite, in conveying their spiritual teachings from each religion, recognizes religion as a universal truth in Tanon society. The last is a customary ritual, and cultural traditions are a means of latency for the people of Tanon Village in forming a harmonious social life.